IMPLEMENTATION OF GOVERNMENT POLICIES IN THE FIELD OF EDUCATION IN THE COMMUNITIES OF THE INNER CHILD ETHNIC COMMUNITY (SAD) - Abdul Fery Eriyanto; Alif Aditya Candra; Heri Usmanto (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This research was motivated by the suboptimal implementation of government policies in the education sector for the Suku Anak Dalam (SAD) community in Sukajadi Village, Bathin VIII District, Sarolangun Regency. Although the government has implemented various educational programs, access to and participation in education remain low due to economic constraints, socio-cultural factors, and inadequate educational facilities and infrastructure. This study aimed to analyze the implementation of government policies in the education sector and identify the factors that hinder their implementation for the Suku Anak Dalam (SAD) community. This research employed a qualitative approach with a descriptive research design. The research subjects were selected using purposive sampling, involving the Sarolangun Regency Education Office, Pundi Sumatra Foundation, the Jenang (traditional leader) of the Suku Anak Dalam, and members of the Suku Anak Dalam community in Sukajadi Village. The primary research instrument was the researcher, supported by observation, interview, and documentation guidelines. Data credibility was ensured through source, technique, and time triangulation, while data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that the implementation of government policies has been carried out through the provision of teachers, community learning centers, educational assistance, and mentoring programs by the government and the Pundi Sumatra Foundation. However, the implementation has not yet been optimal due to low public awareness of the importance of education, family economic limitations, the community's semi-nomadic lifestyle, and limited road access and educational facilities. It can be concluded that the implementation of government policies in the education sector has been carried out but still requires stronger collaboration among stakeholders to ensure the effective and sustainable fulfillment of educational rights for the Suku Anak Dalam community.